2023
DOI: 10.1002/cam4.6483
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bacterial and viral gut communities in healthy and tumoral colorectal tissue usingRNAandDNAdeep sequencing

Ainhoa Garcia‐Serrano,
Dhananjay Mukhedkar,
Emilie Hultin
et al.

Abstract: BackgroundColorectal cancer (CRC) is known to present a distinct microbiome profile compared to healthy mucosa. Non‐targeted deep‐sequencing strategies enable nowadays full microbiome characterization up to species level.AimWe aimed to analyze both bacterial and viral communities in CRC using these strategies.Materials & MethodsWe analyzed bacterial and viral communities using both DNA and RNA deep‐sequencing (Novaseq) in colorectal tissue specimens from 10 CRC patients and 10 matched control patients. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Phages are thought to be key players in bacterial-associated carcinogenesis by modulating the microbial diversity present and CRC development [23]. One study identified four phages in increased abundance in CRC patients [88]. Cancer virotherapy is immunotherapy that uses genetically modified viruses (oncolytic viruses) to selectively target and lyse cancer cells and also facilitates the activity of immune checkpoint inhibitors, which may be beneficial in the treatment of CRC [89].…”
Section: Intestinal Virome and Crcmentioning
confidence: 99%
“…Phages are thought to be key players in bacterial-associated carcinogenesis by modulating the microbial diversity present and CRC development [23]. One study identified four phages in increased abundance in CRC patients [88]. Cancer virotherapy is immunotherapy that uses genetically modified viruses (oncolytic viruses) to selectively target and lyse cancer cells and also facilitates the activity of immune checkpoint inhibitors, which may be beneficial in the treatment of CRC [89].…”
Section: Intestinal Virome and Crcmentioning
confidence: 99%
“…Additionally, in a pathological context, F. nucleatum augments its virulence through the secretion of an amyloid-like adhesin called FadA, utilizing a Fap2-like autotransporter ( Meng et al., 2021 ). In addition, F. nucleatum can enhance drug resistance of tumor cells, inhibit neutrophil infiltration, and ultimately change the tumor immune microenvironment ( Alon-Maimon et al., 2022 ; Garcia-Serrano et al., 2023 ). F. nucleatum is involved in tumor initiation or progression before cancer formation, which regulating the tumor immune microenvironment and promoting the proliferation of tumor-infiltrating immune cells ( Kostic et al., 2013 ).…”
Section: Gut Bacterial Products Associated With Crcmentioning
confidence: 99%